Optimalisasi Peluang Bisnis Untuk Meningkatkan Daya Saing Usaha Fashion: Studi Pada Bisnis Tuku Kelambi - Atikah Salsabila; Idris Idris (Faculty of Economics and Business Diponegoro University, 2025)
This study focuses on efforts to develop sustainable business strategies for the Tuku Kelambi fashion business in Salatiga City. The purpose of this study is to display the current business position using SWOT analysis and formulate strategies that can be applied to overcome internal weaknesses and take advantage of external opportunities. Through this approach, this study seeks to identify effective strategies to improve Tuku Kelambi's competitiveness amidst tight product and marketing competition in the fashion industry.The results of the study indicate that Tuku Kelambi still has market opportunities that must be utilized optimally. However, there are still internal challenges, such as inadequate human resources and weak marketing strategies. Therefore, improving internal aspects such as marketing, services, and managerial aspects to strengthen the competitiveness of Tuku Kelambi's business.The conclusion of this study states that the need for business stabilization and the implementation of business strategies that focus on improving service quality and effective marketing will strengthen Tuku Kelambi's position in the market. With the right strategy, Tuku Kelambi has a great opportunity to develop in the fashion industry that follows the flow of trend models and is competitive.